2010
DOI: 10.1002/pdi.1506
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a staged diabetes management programme in achieving glycaemic goal in a low socio‐economic Hispanic population

Abstract: The aim of this study was to identify the efficacy of a staged diabetes management (SDM) clinic serving a low socio‐economic Hispanic population in achieving glycaemic goal. We analysed prospectively collected data from patients discharged from the clinic in 2008 with an admission HbA1c >8% (64mmol/mol) and >one clinic visit. Adjusted odds ratios (AOR) were determined for factors significantly associated with glycaemic goal achievement. Both those patients who achieved the clinic HbA1c goal of ≤8% (n=277) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is yet to be determined whether or not these improvements can be sustained in primary care. Ruchi Mathur and colleagues(9) found that blood glucose control did not persist for a sample of patients followed a year after return to primary care, although LDL cholesterol reductions were maintained. That study was limited by small sample sizes in the follow-up population and included no comparison group.…”
Section: Diabetes Management In Los Angeles County Department Of Healmentioning
confidence: 99%
“…It is yet to be determined whether or not these improvements can be sustained in primary care. Ruchi Mathur and colleagues(9) found that blood glucose control did not persist for a sample of patients followed a year after return to primary care, although LDL cholesterol reductions were maintained. That study was limited by small sample sizes in the follow-up population and included no comparison group.…”
Section: Diabetes Management In Los Angeles County Department Of Healmentioning
confidence: 99%
“…There is currently a shortage of evidence about healthcare professional‐related barriers to the use of insulin therapy in the management of people with Type 2 diabetes from different ethnic groups in the UK. Where ethnicity is discussed (for example, in relation to Hispanic groups in the USA [15] and in relation to patients from a range of ethnic minority backgrounds the UK [16]), the general view is that healthcare professionals perceive patients as being reluctant to accept insulin therapy because of cultural health beliefs and language barriers. In this paper, we aim to contribute to addressing this knowledge gap by reporting a qualitative exploration of the perspectives of healthcare professionals involved in the management of people with Type 2 diabetes in a multi‐ethnic setting, in Leicester, UK.…”
Section: Introductionmentioning
confidence: 99%